On the possibility of the self-sustaining nuclear chain reaction inside the "Shelter" object at the present time - V. M. Pavlovych; V. A. Babenko (Ядерна фізика та енергетика)
Based on new modern data regarding the state of the fuel-containing masses (FCM) of the "Shelter", as well as taking into account the neutron incident of 1990 and the physical properties of the FCM of the "Shelter", the possibility of the occurrence and development of a self-sustaining chain nuclear fission reaction was considered in the FCM. It is shown that the drying of the FCM can lead to the occurrence of a single neutron burst with an amplitude comparable to the amplitude of neutron oscillations in 1990. It is also shown that the amplitude of the burst can be reduced if the rate of drying of the FCM is increased. The evaluations show that such a burst would have no impact on the environment.